Takaful and mutual insurance : alternative approaches to managing risks - Gönülal, Serap O. (Directions in development (Washington, D.C.). Finance., 2013)
Takaful, which means 'cooperative', is an insurance approach that is instrumental to providing insurance services to Muslims and others with religious objections to aspects of conventional commercial insurance models, specifically interest payments, uncertainty, or gambling kind of transactions.